Use of food delivery apps - Silva, G.; Dias, Á.; Rodrigues, M. (Encyclopedia, 2022)
The pandemic forced both organizations and consumers to make many adjustments to their daily lives. However, due the technological advances that have been seen in recent years, some tools have become much more widely used. Among them are the food delivery applications (FDAs) that experienced an exponential growth during the pandemic.